2010
DOI: 10.1186/1447-056x-9-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of menopausal symptoms using modified Menopause Rating Scale (MRS) among middle age women in Kuching, Sarawak, Malaysia

Abstract: BackgroundMenopausal symptoms can be assessed by several tools, and can be influenced by various socio-demographic factors.ObjectivesTo determine the commonly reported menopausal symptoms among Sarawakian women using a modified Menopause Rating Scale (MRS).MethodsBy using modified MRS questionnaire, 356 Sarawakian women aged 40-65 years were interview to document of 11 symptoms (divided into somatic, psychological and urogenital domain) commonly associated with menopause.ResultsThe mean age of menopause was 51… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
130
4
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(171 citation statements)
references
References 33 publications
(51 reference statements)
28
130
4
4
Order By: Relevance
“…[3] Studies conducted at various other countries showed mean age of menopause slightly higher as compared to Indian studies, Malaysia (51.2 years), Thailand (48.7 years), and Singapore (49.1 years). [12][13][14] Menopause-related symptoms assessed by present study were quite similar to other studies. In the study conducted at Bihar [15] using same rating scale, 112 (40.1%) women found to have episodes of hot flashes, sweating, and/or night sweats in the preceding 4 weeks.…”
Section: Discussionsupporting
confidence: 90%
“…[3] Studies conducted at various other countries showed mean age of menopause slightly higher as compared to Indian studies, Malaysia (51.2 years), Thailand (48.7 years), and Singapore (49.1 years). [12][13][14] Menopause-related symptoms assessed by present study were quite similar to other studies. In the study conducted at Bihar [15] using same rating scale, 112 (40.1%) women found to have episodes of hot flashes, sweating, and/or night sweats in the preceding 4 weeks.…”
Section: Discussionsupporting
confidence: 90%
“…A study which was done by Rahman et al, showed that the urogenital symptoms were significantly higher in the postmenopausal group as compared to those in the menopause transition group. The psychological symptoms were significantly higher among the perimenopausal women as compared to those among the postmenopausal women [27]. In our study, the vasomotor symptoms and the sexual symptoms were more prominent in the menopause transition group than in the early and late post menopausal groups.…”
Section: Discussioncontrasting
confidence: 47%
“…In addition Ashrafi et al (2010) [29] showed that night sweats, joint and muscle pain and hot flashes are the most common symptoms associated with menopause in Iranian women. These findings were also noted by Rahman et al (2010) [30] emphasized that the frequency of sexual problems, bladder problems and vaginal dryness were experienced mainly by premenopausal and postmenopausal group of women and it was also significant statistically in comparison to other menopausal status. The most prevalent psychosocial symptom in the present study was; poor memory that agrees with results of many studies, which indicated that the most common and severe symptom that was reported by women was poor memory [25,31,32] .…”
Section: Discussionmentioning
confidence: 64%